A system equation model a comparative study for G-7 countries - Antonios Adamopoulos; Athanasios Vazakidis (SPOUDAI - Journal of Economics and Business, 2019)
This paper investigates the relationship among investments, exports and economic growth for G-7 countries for the period 1975-2017, except for Germany (1991-2017), estimating a simultaneous system equations model. The Group of Seven countries (G7) is a group consisting of Canada, France, Germany, Italy, Japan, United Kingdom, and USA regarded as the most advanced countries worldly, representing 58% of the global net wealth. The purpose of this paper is to examine the long-run relationship between the examined variables applying the two-stage least squared method. Finally, a system equation model is estimated for G7 countries applying a Monte Carlo simulation method, in order to find out the predictive ability of the equation model. The results of this paper indicated that there is a positive relationship between investments, exports and economic growth taking into account the negative indirect effect of inflation rate and positive indirect effect of industrial production index on economic growth. Furthermore, the model is very well simulated, since the simulated values are close to actual values of examined variables.
Keywords: O11; C22; 330; Economic growth; exports; investments; simulation; G7 countries